The essence and structure of the development of communicative competence of future specialists in psychologyʺ - Shkurko , A. (Problems of Engineer-Pedagogical Education, 2024)
The article analyzes the structures of communicative competence of future psychology specialists by various scholars. The author comes to the conclusion that there is no clear structure which would consider the specifics of the professional activity of psychology specialists and would contribute to the full development of their communicative competence. It has been found that the development of communicative competence of future psychology specialists involves the development of both personal and professional qualities, and the process itself should be implemented in the unity of theoretical training in the norms and culture of communication and practical training - the ability to apply knowledge, skills, select the necessary effective technologies and techniques during live communication with any interlocutor. To clarify the content of the development structure of future psychology specialists' communicative competence, a survey of psychologists working in the specialty and research and teaching staff of higher educational institutions has been conducted. The experts identified the competencies that, according to them, should be acquired by future psychology specialists. The result of this survey was the identification of key competencies: motivational and value, conflict, regulatory, prognostic, reflective, gnostic, evaluative, perceptual. The author's structure for the development of future psychology specialists' communicative competence, consisting of four components and corresponding competencies, has been highlighted. The author refers to the socio-volitional component as regulatory and perceptual competencies aimed at forming control skills in the process of communication. The integrative-activity component includes technological, conflict and prognostic competencies that will provide the ability to apply various methods and technologies to resolve conflicts and problems through communication. The cognitive-motivational component provides for the development of motivational-value and gnostic competencies to maintain motivation for the process of developing communicative competence. Reflective and speech competencies are reflected in the communicative and reflective component of the structure. The unity of the structural components will ensure the comprehensive development of future psychology specialists as qualified professionals with a high level of communication competence.